Analysis of the Influence of Growth Opportunities and ISO 14001 Certification on the Level of Carbon Emission Disclosure - Hermiyetti, Hermiyetti; Usmar, Usmar (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the effect of growth opportunities and ISO 14001 certification on the level of carbon emission disclosure in companies listed on the Indonesia Stock Exchange (IDX). Carbon emissions have become a global concern as demands for environmental accountability and transparency in corporate practices increase. This study employs a quantitative approach using multiple linear regression, based on secondary data obtained from annual reports and sustainability reports of 70 companies during the period 2019–2023. Carbon emissions disclosure is measured using GRI G4-EN15 to G4-EN21 indicators, while growth opportunity is measured through the market-to-book equity ratio, and ISO 14001 certification is categorized as a dummy variable. The results indicate that growth opportunities and ISO 14001 certification have a positive and significant effect on the level of carbon emissions disclosure. Together, these two variables explain 37.5% of the variation in corporate carbon disclosure. These findings indicate that companies with high growth prospects and formal environmental management systems are more likely to disclose carbon emissions information openly as part of their sustainability strategy and public legitimacy. This study contributes theoretically to the environmental accounting literature and offers practical implications for regulators, investors, and companies in promoting more transparent carbon emissions management and reporting